Eosinophilia – A rare possible adverse reaction during anti-tumor necrosis factor-alpha therapy for psoriasis. (3rd March 2016) - Chiriac, Anca; Brzezinski, Piotr; Stolnicu, Simona; Podoleanu, Cristian; Moldovan, Cosmin; Molnar, Calin; Taranu, Tatiana
Abstract: The current use of tumor necrosis factor (TNF)-alpha inhibitors in rheumatological, dermatological and gastroenterological diseases has increased considerably in recent years. Different reports have been communicated regarding specific risks and side effects during treatment with TNF-alpha inhibitors. Eosinophilia has been linked to TNF-alpha inhibitors by several recent reports, although it is not listed as a possible adverse reaction in the product information of the drug. The aim of the present study was to evaluate the eosinophil count in patients diagnosed with psoriasis and treated with adalimumab. Based on the results of the present study, eosinophilia remains a rare adverse reaction during psoriasis treatment with TNF-alpha antagonists.